REVIEW ARTICLE: THE IMPORTANCE OF HALAL VALIDATION OF INGREDIENTS AS CRITICAL PARAMETER DURING HALAL AUDITS - Sunaryo, Endang S.; Mardiah, Mardiah; Rahmawati, Siti Irma (Universitas Djuanda, 2019)
As one of the biggest numbers of Muslim population in the world, Indonesia considering as one of potential market for food and beverages. Latest 3 years data showed products especially Food & Beverages produced by small & micro industries increased tremendously compared to medium & large enterprises. Among of Asean countries, the growth of consumer goods market in 5 years (2012 – 2017) increased significant (10 %) particularly packaged food and soft drinks. Therefore more challenges related with validity of raw material/ingredients Halal certification (its authenticity), validity of GMP and HACCP certification to guarantee “thoyyiban” during food processing and validity of halal supply chain from farm to table (documents authenticity). Interesting facts that due to scarcity of getting halal ingredients, producers tends to sifting to chemical process in orders to make halal audit easy. Unfortunately they ignore the sifting may create another health concern. Others concern are incompletely requirement such as Halal Certificate of ingredients, Certificate of Analysis, Material Safety Data Sheet and Food Processing Chart. Those documents often issued by traders instead of its manufactures (supposed to be). To improve and fasten the innovation, we propose some cooperation and network among ASEAN Halal institutions. Keywords: halal validation, ingredients, critical parameter, halal audit